Risk factors, presentations, associated anomalies, and outcomes of patients with encephalocele - Nawzhin Jange Jalyzada; Ari Sami Hussain Nadhim; Nabaz Muhamad Mustafa (Advanced Medical Journal)
Background and objectives: Encephalocele is a rare neural tube birth defect. Aim of this study was to find the risk factors and associated anomalies of patients with encephalocele, and its outcomes.